Manajemen Sistem Pengambilan Keputusan (Gagasan Mengilmiahkan Proses Pengambilan Keputusan) - juen juen juen (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2018)
The fifth generation management emerged and developed in tune with the emergence of high-tech technology, information superhighway, and digitec economy so that the concept of the importance of building competitiveness through knowledge emerged. Within this framework, the teachings of fifth generation management should be applied in the lives of both profit and non-profit organizations including education. Decision making as one of the elements of the organizational sub-system, needs to adjust to the concept in question. Therefore, decision making must also be related to how decision making within the organization - including education - must also be scientifically accountable as the rules of the fifth generation management teachings.